AKTIVITAS ANTIFUNGI EKSTRAK METANOL DAUN SALAM (Syzygiumpolyanthum [Wight] Walp.)TERHADAP PERTUMBUHANHortaea werneckii(T1)SECARA IN VITRO - Sumi, Sumi; Wardoyo, Elvi Rusmiyanto Pancaning; Rahmawati, Rahmawati (Jurnal Protobiont, 2020)
Hortaea werneckii is a fungus causes of tinea nigra. Plants that are known to have antifungal compounds are bay leaves (Syzygium polyanthum). This study was aimed to determine the best concentration of the methanol extract from bay leaves (S. polyanthum) can inhibit the growth of Hortaea werneckii (T1) in vitro. This study used a completely randomized design (CRD) with treatment levels that consisted of concentrations of 20, 25, 30, 35 and 40%, negative control (sterile distilled water) and positive control (ketoconazole 2%). The antifungal activity test was carried out using the Kirby-Bauer method. Based on the results study showed that concentration 30% is the best concentration in inhibit fungal growth Hortaea werneckii (T1).